THEOLOGICAL HIGHER EDUCATION LEADERSHIP CHALLENGES AND SOLUTIONS AMIDST THE COVID 19 PANDEMIC - Ayuk Ausaji Ayuk (Scriptura Indonesia, 2022)
A hermeneutical study on higher education response to the crisis in education during the pandemic. It was discovered that higher educational institutions were able to handle the crisis of the time creatively and successfully as the positive points of the challenges outweigh the negative points of the situation. The negative experiences included: Poor internet connection, lack of necessary technological equipment, online education health related issues, and home distractions. Whereas the positive points are as follows: The reawakening of the online learning system, a viable alternative to the classroom, sociability, opportunity for parents to nurture their children while studying, practical and safe access to education, and the future of education online. This shows clearly that the challenge became an opportunity in disguise by creating an added means of providing an opportunity for people to have access to education. The study has made educators aware of the fact that online education is no more a dream very far away, but rather a reality at the doorstep if we are willing to take advantage of it and expand our classrooms far beyond the enclave of our educational institution’s campuses.